2017
DOI: 10.1053/j.jfas.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneocuboid Distraction Arthrodesis With Synthetic Bone Grafts: Preliminary Results of an Innovative Bone Grafting Procedure in 13 Patients

Abstract: Calcaneocuboid distraction arthrodesis (CCDA) is regarded as an effective method for reconstructing adult-acquired flatfoot deformity. In the present study, we present our experience with newly developed rigid β-tricalcium phosphate wedges to treat CCDA to better understand the outcomes of this synthetic bone grafting procedure. A total of 13 feet in 13 patients underwent CCDA with synthetic bone grafts. One male (7.69%) and 12 females (92.31%), with a mean age of 65.07 ± 11.83 (range 36 to 77) years, were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Several studies have suggested that adding stability with a locking plate and screws may stabilize the environment sufficiently for the graft to heal [2,17,18,25,36]. The etiology of graft collapse is secondary to both mechanical and biologic factors [2,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that adding stability with a locking plate and screws may stabilize the environment sufficiently for the graft to heal [2,17,18,25,36]. The etiology of graft collapse is secondary to both mechanical and biologic factors [2,39].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated CCDA has been shown to minimally limit hindfoot motion while eliminating the risk of CC subluxation, increased CC joint pressure, and subsequent degenerative changes when performing a calcaneal lengthening osteotomy [19][20][21][22][23][24]. Historically, this procedure was performed without supplemental fixation but was prone to poor results due to graft collapse, nonunion, and subsequent loss of correction [2,15,25,26]. In 2010, our institution began to supplement this procedure with the use of locking plate fixation at the discretion of the attending surgeon in an effort to improve healing rates, reduce graft failure, and optimize correction.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 Furthermore, other orthobiologics and other synthetic bone grafts including cellular bone allograft containing mesenchymal stem cells, bone marrow aspirate, platelet-derived growth factor, platelet-rich plasma, bone morphogenetic protein, fatal tissue, and demineralized bone matrix are also recommended for foot and ankle surgery. 18 20 However, at present, there are many actual cases for which allografts and other orthobiologics are not available in Japanese hospitals or Japanese health insurance systems. In such situations, combination of calcaneal bone with IP-CHA (NEOBONE®) was also useful for relatively larger bony defects (1.5–2.0 cm) in subtalar joint.…”
Section: Discussionmentioning
confidence: 99%
“…The CAp HC blocks that were fabricated using debinding temperatures of 600, 650, and 700 °C were labeled as HC-600, HC-650, and HC-700, respectively. A high-strength clinically used β-TCP block with a three-dimensional (3D) porous structure (Olympus Terumo Biomaterials Co., Ltd., Tokyo, Japan; Osferion Marvelous) was selected as the control block because it is widely applied in orthopedic surgery of loading limbs. …”
Section: Methodsmentioning
confidence: 99%
“…Generally, synthetic bone blocks are used to clinically treat the defect in osteotomy surgeries of loading limbs. Therefore, the effects of the pore characteristics in blocks on mechanical strength, osteoconductivity, and bioresorbability should be evaluated by implanting blocks in load-bearing segmental defects. However, previous studies have investigated the effect of the pore characteristics in synthetic bone blocks on bone reconstruction using nonload-bearing bone defects. Furthermore, while these studies did not evaluate the mechanical strength of the blocks, they did investigate osteoconductivity and bioresorbability.…”
Section: Introductionmentioning
confidence: 99%